PENGARUH PEMBERIAN TEPUNG TONGKOL JAGUNG FERMENTASI SEBAGAI PAKAN TAMBAHAN TERHADAP PERFORMA ITIK PEDAGING JENIS HIBRIDA: THE EFFECT OF FERMENTED CORN COB FLOUR AS SUPPLEMENTARY FEED ON THE PERFORMANCE OF HYBRID BROILER DUCKS - Ramadhan , Gustiar Cahya; Mulyono, Ali Mursyid Wahyu; Husein, Muhammad (Universitas Boyolali, 2026)
This study aims to analyze the performance of hybrid broiler ducks with the addition of fermented corn cob flour to their feed. An experimental method was used for this study. This study used 36 1-week-old hybrid broiler ducks and were raised for 4 weeks in a completely randomized design (CRD) with 4 treatments and 3 replications. The hybrid ducks were fed fermented corncob meal at percentages of 0%, 2%, 4%, and 6% as part of the treatment. Feed Consumption (FI), Body Weight Gain, and Feed Conversion Ratio (FCR) were some of the variables examined. Analysis of Variance (ANOVA) was used to examine the research data, and Duncan's Multiple Range Test (DMRT) was used to test the results at a 5% significance level. The research findings showed that Feed Consumption (FI), Body Weight Gain, and Feed Conversion Ratio (FCR) of hybrid ducks were not affected by the addition of fermented corncob meal to the feed.